2020
DOI: 10.1177/0954408920906274
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional squeezed flow of aqueous magnetite–graphene oxide hybrid nanofluid: A novel hybridity model with analysis of shape factor effects

Abstract: In the present article, we intend to study quasi-analytically the unsteady three-dimensional squeezed flow of the magnetite–graphene oxide/water hybrid nanofluid inside a rotating channel with two horizontal and parallel sheets, in which the lower sheet is stationary, stretchable, and permeable, while the upper sheet is moving and impermeable. Our methodology is based on the single-phase Tiwari–Das hybrid nanofluid model considering nanoparticles and base fluid masses instead volume concentration of first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…With greater nanoparticle volume fraction there is however a slight decrease in temperatures for water-TiO 2 (Figure 5A) whereas there is a more prominent reduction in temperature for ethylene glycol-TiO 2 nanofluid (Figure 5B). The general thermal enhancement properties of nanofluids, as predicted by many researchers, for example, [24][25][26]32 are therefore not computed for convergent channels.…”
Section: Validation With No-slip Case and Absence Of Viscous Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…With greater nanoparticle volume fraction there is however a slight decrease in temperatures for water-TiO 2 (Figure 5A) whereas there is a more prominent reduction in temperature for ethylene glycol-TiO 2 nanofluid (Figure 5B). The general thermal enhancement properties of nanofluids, as predicted by many researchers, for example, [24][25][26]32 are therefore not computed for convergent channels.…”
Section: Validation With No-slip Case and Absence Of Viscous Heatingmentioning
confidence: 99%
“…Various applications of the Tiwari-Das nanofluid model 26 have been analyzed by a number of researchers. [29][30][31][32] Recently, Saleem and Heidarshenas 33 reported an examination of exergy in a wavy wall microchannel heat sink by using various nanoparticles in fluid flow. They used commercial Ansys fluent software.…”
Section: Introductionmentioning
confidence: 99%
“…Their contributions show the anti-tumor effect of particles which indicate that they could be a cost-effective cancer therapy then another treatment 19 . Some recent studies regarding hybrid nanofluids flows with different geometries are investigated by Zainal et al 20 22 and Dinarvand 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Waini et al 25 reported unsteady flow and heat transfer in Al2O3–Cu HNF through a stretching/shrinking layer and the local Nusselt number grows with rising concentration of Cu. Dinarvand and Rostami 26 investigated three‐dimensional (3D) squeezed flow in Fe3O4–Go/water HNF and suggested the single‐phase mass‐based technique for quasi‐analytical simulation of HNFs. In addition, more relevant numerical and theoretical studies about HNF and convective heat transfer have been reported 27–31 …”
Section: Introductionmentioning
confidence: 99%